(untitled) (Journal of Human Sciences, 2021)
This study aimed to identify the causes of administrative negligence in the General Authority of the Social Solidarity Fund. This is done by gathering the point of view of the heads of departments and units of Sebha branch. The sample size was (43) department heads and one unit head. The tool consisted of (30) expressions. The (T) test is used in the statistical analysis. The one-way variance test is also used. The two researchers relied on the descriptive-analytical approach. The results of the study ensured the following: There are statistically significant differences for the reasons for administrative negligence in the General Authority of the Social Solidarity Fund, from the point of view of the heads of departments and units in the General Authority. This is happening according to the degree of freedom and these differences are classified in favour of the sample members. There are no statistically significant differences to the reasons for administrative negligence in the General Authority of the Social Solidarity Fund, from the point of view of the heads of departments and units, due to the gender variable. There are no statistically significant differences to the causes of administrative negligence in the General Authority of the Social Solidarity Fund from the point of view of the heads of departments and units. This is due to the variable of social status. Statistically significant differences to the reasons for administrative negligence in the General Authority of the Social Solidarity Fund from the point of view of the heads of departments and units are due to the variable, years of service. These differences are in favour of the heads of the departments and units with experience of 25 years and above.